Development of Medical and Health Science Collection to Support Scientific Integration at UIN Syarif Hidayatullah Jakarta - Lolytasari Lolytasari; Nurul Hayati; Imas Fathonah (Alexandria: Journal of Library and Information Science, 2024)
Integrating knowledge is familiar to the State Islamic University, which has a Faculty of Medicine and Health Sciences. One of the problems that arise is the library's role as an institution that manages knowledge and can meet the information needs of the academic community in the form of collections in various media, namely printed and online. Therefore it is necessary to evaluate the collection development provided by the library. So the purpose of this research is to analyze how far the library collections of the Faculty of Medical Sciences and the Library of Health Sciences have developed in supporting scientific integration efforts at UIN Syarif Hidayatullah Jakarta. The research approach used is descriptive qualitative. This study found that library managers carried out collection development by considering the courses and study programs in the faculties of health and medicine. The library focuses on gathering resources and materials relevant to the fields of health and medicine and paying attention to related aspects of Islamic ethics and culture. So the more relevant the collections provided by the library, the higher the quality of knowledge and information library users need.